العلاقة البينية بين علمي التاريخ والآثار مدينة قلهات الإسلامية: حالة دراسية - القدحات، محمد عبدالله أحمد; دغلس، خالد أحمد (جامعة السلطان قابوس - كلية الآداب والعلوم الاجتماعية, 2018)
This study aims to clarify the relationship between archaeology and history. Archaeological evidence can bear witness to historical events. Such events can be discovered, studied, and classified by archaeologists and presented to historians as authentic material, especially in the absence of written sources. Thus, the joint work between archaeologists and historians could help to reformulate past events into coherent historical records The Islamic city of Qalhat is taken as an example in this study. It is almost absent from historical sources although it was a very important port city during the 13th to 17th century. On a very few occasions, it was mentioned by some travelers who visited the city and described it as a living and flourishing city. However, so few and such short records do not provide enough evidence of the history of the city. Only archaeology can narrate the complete story of the city where the earliest and latest phases of occupation were fully uncovered. Archaeological excavations revealed in detail the high level of architecture that the inhabitants of Qalhat had and how the city was well organized and divided into different quarters as well as the fortification system and an international network of trade relations. All of this archaeological evidence will enable historians to rewrite the history of the Islamic city of Qalhat based on solid grounds.
تهدف الدراسة إلى بيان العلاقة التكاملية بين علمي التاريخ والآثار؛ فالآثار هي الشاهد الحقيقي على وقوع الحدث التاريخي؛ ولذا فإن الكشف عنها ودراستها وتصنيفها يجعلها مادة أصيلة للباحث التاريخي لا سيما في ظل غياب المصادر المكتوبة، وبالتالي فإن العمل المشترك بين الآثاري والمؤرخ ينتج نصا تاريخيا متماسكا، ومدعما بأدلة مادية ملموسة، ولعل مدينة قلهات الإسلامية خير مثال على ذلك؛ فالمادة المدونة عن تاريخها الإسلامي لا تتعدى عدة روايات جاءت في كتب الرحالة والجغرافيين الذين زاروا المدينة ووصفوها بالعامرة، والمزدهرة اقتصاديا، لكن تلك المادة المبتورة لا يمكن منها تدوين تاريخ المدينة الإسلامي؛ لذا فإن المكتشفات الأثرية التي تم العثور عليها في العقود الماضية، قد أماطت اللثام عن بعض من تاريخ المدينة الحضاري، ومستوى الحياة الاقتصادية لسكانها، ويتضح ذلك من بقايا القطع الفخارية والبورسلان والسيراميك التي كانت تستخدم في مناحي مختلفة من حياة أهل المدينة، كما أن الكشف عن معالم المدينة، مثل: الأسوار والحارات والمسجد الجامع، تمكن الباحث من دراسة خطط المدينة وشوارعها والمرافق العامة فيها.
Keywords: الدراسات التاريخية -- التاريخ الإسلامي -- الآثار -- المعالم التاريخية -- مدينة قلهات الإسلامية -- سلطنة عمان -- المجتمع العماني